The Impact Work Discipline, Financial Compensation, Organizational Commitment on Employee Performance at Ganesha Utama - Kadek, Bramdhika Ada; Rahmat Yanuary; Vitalia Fina Carla Rettobjaan; I Ketut Johny Pramanda Putra (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
In today's global competition, the world of work requires individuals who are forward-thinking, intelligent, innovative, and able to work with high performance to face the times. This study aims to analyze the factors that influence employee performance at Ganesha Utama Savings and Loan Cooperative (KSP) in Denpasar, focusing on work discipline, financial recovery, and organizational commitment. This research data is primary data obtained through questionnaires, with a total of 33 respondents. The data analysis techniques used include quantitative analysis, classical assumption test, multiple linear regression analysis, F test, and T test. The results of the F test show that work discipline, financial recovery, and organizational commitment simultaneously have a positive and significant effect on the performance of KSP Ganesha Utama employees. The T test results show that the work discipline variable has a positive but insignificant effect on employee performance, while the financial recovery variable has a positive and significant effect. Organizational commitment variables also have a positive but insignificant effect on employee performance. The implications of this study indicate the importance of improving financial aspects in supporting employee performance, although work discipline and organizational commitment remain relevant in efforts to improve performance. These results provide a basis for KSP Ganesha Utama to prioritize strategies to improve financial well-being as well as employee performance.